Knowledge, Attitudes and Practices of Medical Residents towards Healthcare Ethics in the Islamic Hospital, Jordan - Fayez Abdulrazeq; Abdulwahab Al-Maamari; Walaa Ameen; Alaa Ameen (University of Science and Technology, Sana'a, 2019)
Objective: To assess the baseline knowledge, attitudes and practices of medical residents in the Islamic Hospital in Amman, Jordan towards healthcare ethics. Methods: This was a cross-sectional study conducted among 111 medical residents in the Islamic Hospital in the period from February to April 2017. Data were collected using a self-administered questionnaire, and Pearsons chi-square test was used to test the statistical significance of differences between male and female medical residents at P values <0.05. Results: The majority of the respondent medical residents (76.6%) were aware of the content of the Hippocratic Oath. Ethical dilemmas at some point during clinical practice were reported by 68.0% of medical residents; however, only 6.3% reported encountering such dilemmas on a daily basis. Books, lectures and Media were the most frequent sources used by medical residents for learning about healthcare ethics, while supervisors, chiefs of residents and heads of departments were the most frequently preferred for consultation on both ethical and legal problems. The majority (91%) of respondents showed an interest in learning healthcare ethics. However, gaps in knowledge and negative attitudes were observed. Statistically significant differences between male and female residents were found in the issues related to paternalism in case of disagreement with patients/ families, seeking consent for surgeries but not for tests or medications as well as disclosure of tuberculosis-positive status. Conclusions: There are some gaps in knowledge and negative attitudes towards healthcare ethics among medical residents, where some residents are even unaware of the content of the Hippocratic Oath. Because a substantial proportion of medical residents encounter ethical problems at some point during their clinical practice, there is a necessity to incorporate ethics education into medical curricula, which should be directed at practical real-world dilemmas. Future physicians must learn how to adhere to the four basic principles of healthcare ethics (autonomy, beneficence, justice and nonmaleficence) early in their career.